APLIKASI CRM JASA SERVIS AIR CONDITIONER PADA JAYA SERVICE BERBASIS ANDROID - Samuel Van Basten Manurung; Indra M. Sarkis Simamora; Rio Aprijal Manurung; Asaziduhu Gea (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
In the current era, many Android applications have been used in the process of requesting goods or services that can facilitate activities, especially placing orders, especially in the case study below using services made by the company CV. Jaya Service, this service is difficult to promote by CV. Jaya Service because it only posts small banners on the side of the road so that the income level of this ac service does not increase or even decrease. In addition, the current process, customers always order ac service directly to the location, this takes a long time, and in the sales inspection process it becomes difficult and takes a long time. Customer relation management is needed to maximize activities or Many marketing items, sales, and sales processes are currently done automatically. Analytical customer relation management is very useful in exploiting data from customers in order to increase the quality value of the company, through a CRM business strategy that will be combined with a process, humans, with technology. assist in the process of adding customers related to sales, converting the company to permanent members, and maintaining existing permanent members, satisfied and loyal permanent members. This study aims to design a CRM Service AC Service on Android-based Jaya Service. From the results of this study, the system built can make it easier for customers to order ac service easily directly via cellphones and can provide convenience to Jaya Service in seeing incoming orders and the results of service order transactions.